Education for public good in the age of coloniality: Implications for pedagogy (Journal of Decolonising Disciplines, 2020)
This paper critically reviews the theoretical foundations of the concept ‘education for public good’, revealing its analytical and practical limitations, inadequacies and detrimental effects in South Africa. The paper shows how an uncritical embracing of this concept in the education discourse continues to undermine hard-earned democratic gains. Coloniality, I argue, continues to ‘devour’ all well-intentioned postcolonial/post-apartheid educational policies. A truly decolonial project has the power to dismantle pedagogical practices and classroom traditions that evolved in the west to favour the elite while marginalising the majority. An alternative to education for public good is thus presented: education for common good. The Reading to Learn pedagogy is presented as an ‘offspring’of the ‘education for common good’ concept. I highlight how this position engenders classroom practices that create conditions for epistemological access to success for all learners, regardless of their socioeconomic background.
Keywords: education for public good; coloniality; transmission of curriculum content; education for common good; Reading to Learn Pedagogy; literacies for curriculum acquisition